2010
DOI: 10.1080/00049180903535535
|View full text |Cite
|
Sign up to set email alerts
|

Postcards from Somewhere: ‘marginal’ cultural production, creativity and community

Abstract: This paper focuses on a case study of local postcard production in a rural community in Western Australia. Drawing on in-depth interviews with key producers of these postcards, the analysis presented explores perceptions of and contexts for the emergence of this production, in turn examining the notion of 'creativity' articulated and privileged by this cultural work. Connections are identified between the making of postcards, the broader historical field of local cultural work and the construction of community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Oulu, the biggest city in Northern Finland with about 194,000 inhabitants, is located between 100 to 700 km from the case study sites (City of Oulu, 2014). So far research on actors from creative fields outside large cities includes examples from suburban regions (Hracs, 2009;Bain, 2013), cities of 100,000 inhabitants or more that are located further than three hours' drive from other cities (Bennett, 2010;Brennan-Horley, 2010;Gibson et al, 2010;Verdich, 2010), and small cities (here less than 70,000 inhabitants) within a three-hour drive to a major city (Curtis, 2010) or further away from larger cities (Andersen, 2010;Mayes, 2010). The latter examples resemble the Lapland case the most.…”
Section: Artists Of Finnish Laplandmentioning
confidence: 96%
“…Oulu, the biggest city in Northern Finland with about 194,000 inhabitants, is located between 100 to 700 km from the case study sites (City of Oulu, 2014). So far research on actors from creative fields outside large cities includes examples from suburban regions (Hracs, 2009;Bain, 2013), cities of 100,000 inhabitants or more that are located further than three hours' drive from other cities (Bennett, 2010;Brennan-Horley, 2010;Gibson et al, 2010;Verdich, 2010), and small cities (here less than 70,000 inhabitants) within a three-hour drive to a major city (Curtis, 2010) or further away from larger cities (Andersen, 2010;Mayes, 2010). The latter examples resemble the Lapland case the most.…”
Section: Artists Of Finnish Laplandmentioning
confidence: 96%
“…Moreover, in some of these locations, it is extremely difficult to identify industry sectors resembling the creative industries as they have come to be understood internationally. More vernacular understandings of creativity are required, outside of standardized industry classification schemes, embedded in the social life of rural and industrial places -to capture practices as diverse as community gardening, Aboriginal hip-hop, knitting groups, custom car design, postcard illustrations, clothes swap parties and food tourism (see Edensor et al, 2009;Mayes, 2010;Warren & Evitt, 2010). Our shift towards cultural assets in the CAMRA project was an attempt to escape the framing confines of "creative" industry research and instead open opportunities for communities to define what creativity might be and, more broadly, what cultural aspects, features, attitudes or even feelings pervade their place and are valued accordingly.…”
Section: Mapping Creative Darwin: the Anatomy Of Creativity In The Citymentioning
confidence: 98%
“…There is now also a second wave of research on the cultural and creative industries that distances itself from the boosterish and neo‐liberal tendencies of Richard Florida‐inspired consultancy reports, exploring instead creativity in working‐class contexts (Jayne, 2004; Warren and Gibson, in press) and forms of vernacular creativity beyond money‐making activities (Edensor et al ., 2009; Ettlinger, 2010) – echoing earlier ethnographic work on working‐class youth subcultures which sought to theorise creativity in everyday life (Willis, 1990). Distinctly Australian examples include rural community festivals (Gibson et al ., 2010), postcard production (Mayes, 2010), and hand‐making surfboards (Warren and Gibson, 2011) – the latter in particular linked to debates about crafting, place identities, emotion, and precarious labour (Christopherson, 2008). As Mayes' (2010, 19) research on postcards produced by a remote Western Australian community revealed, creativity is frequently ‘quotidian activity in the service of daily problems (such as lack of local postcards, the need to keep busy, fundraising) with an emphasis not so much on commerce or novelty but rather on “usefulness” ’.…”
Section: The Cultural Into the Economicmentioning
confidence: 99%
“…Distinctly Australian examples include rural community festivals (Gibson et al ., 2010), postcard production (Mayes, 2010), and hand‐making surfboards (Warren and Gibson, 2011) – the latter in particular linked to debates about crafting, place identities, emotion, and precarious labour (Christopherson, 2008). As Mayes' (2010, 19) research on postcards produced by a remote Western Australian community revealed, creativity is frequently ‘quotidian activity in the service of daily problems (such as lack of local postcards, the need to keep busy, fundraising) with an emphasis not so much on commerce or novelty but rather on “usefulness” ’. Others have documented side effects of the growth of the creative economy in a broader urban and social context.…”
Section: The Cultural Into the Economicmentioning
confidence: 99%